Tubal Ectopic Pregnancy: From Diagnosis to Treatment - Dimitrios Papageorgiou; Ioakeim Sapantzoglou; Ioannis Prokopakis; Eleftherios Zachariou (Biomedicines, 2025)
The most frequent form of ectopic pregnancy, known as tubal pregnancy, leads to a dangerous situation where the fertilized ovum implants inside a fallopian tube, which can result in tubal rupture and severe bleeding. The purpose of this narrative review is to evaluate all existing data regarding epidemiology, risk factors, pathophysiology, clinical presentation, diagnosis, and management of tubal ectopic pregnancy in order to provide a comprehensive understanding of this common yet difficult clinical condition. Prior ectopic pregnancy, together with tubal pathology and assisted reproduction, represent the main risk factors for this condition. The diagnosis relies on serial β-hCG tests combined with transvaginal ultrasonography, but laparoscopy serves as the diagnostic tool for cases with uncertain results. The treatment plan depends on the fallopian tube integrity, along with the patient’s hemodynamic condition. Patients with unruptured pregnancies who are hemodynamically stable receive methotrexate treatment as the preferred option, but surgical intervention with salpingectomy or salpingostomy becomes necessary in case of tubal rupture or when medical treatment fails. The development of laparoscopic procedures has led to better results and improved possibilities for fertility preservation. The psychological effects on patients require both counseling and follow-up care. Early detection, along with personalized management, helps decrease maternal complications and optimize reproductive outcomes.